2008
DOI: 10.1158/1078-0432.ccr-08-1124
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I-II Study to Determine the Maximum Tolerated Infusion Rate of Rituximab with Special Emphasis on Monitoring the Effect of Rituximab on Cardiac Function

Abstract: Purpose: This phase I infusion rate escalation trial was undertaken to evaluate the maximum applicable infusion rate for rituximab without steroid premedication in patients having received one previous rituximab infusion. Experimental Design: Cohorts of at least three patients were assigned to rituximab with or without concomitant chemotherapy. The initial infusion rate was 200 mg/h in the first cohort, and was increased by 100 mg/h in each subsequent cohort to a maximum of 700 mg/h. In each patient the infusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 18 publications
0
23
0
Order By: Relevance
“…Only 1 patient in the latter study received rituximab as monotherapy. A phase I-II study by Siano et al [9] has demonstrated that rituximab can be administered safely at 700 mg/h without steroid premedication. Larger studies can be conducted to investigate the safety of a 60-min infusion of rituximab without corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…Only 1 patient in the latter study received rituximab as monotherapy. A phase I-II study by Siano et al [9] has demonstrated that rituximab can be administered safely at 700 mg/h without steroid premedication. Larger studies can be conducted to investigate the safety of a 60-min infusion of rituximab without corticosteroids.…”
Section: Discussionmentioning
confidence: 99%
“…5 Indications included idiopathic thrombocytopenic purpura (n = 9), chronic inflammatory demyelinating polyneuropathy (n = 5), thrombotic thrombocytopenic purpura (n = 3), cold agglutinin disease (n = 2), hemolytic anemia (n = 2), acquired hemophilia (n = 1), and Sj€ ogren syndrome (n = 1). b Indications included chronic lymphocytic thyroiditis (n = 1), monoclonal gammopathy (n = 1), and Hodgkin lymphoma (n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…To examine the latter, a phase I-II study examining infusion rates and cardiac function revealed only one case of asymptomatic changes on electrocardiogram [10], but this study also excluded patients with any preexisting cardiac conditions. Acute coronary ischemia precipitated by rituximab in those with a history of cardiac disease or those with cardiac risk factors has been described in recent case series and case reports [11, 12].…”
Section: Discussionmentioning
confidence: 99%